2012
DOI: 10.1563/aaid-joi-d-11-00058
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Loading of Single Post-Extractive Implants in the Anterior Maxilla: 12-Month Results From a Multicenter Clinical Study

Abstract: The purpose of the study was to evaluate survival and peri-implant bone levels of single, immediately loaded post-extractive implants in the anterior maxilla 12 months after implant placement. Thirty-six consecutive patients from 3 study centers were included in the study. The concerned sites were upper premolars, canines, and incisors. For each patient the following data were recorded: reason for tooth extraction, bone quality, implant size, and final insertion torque. Implants were placed using a flapless te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(116 citation statements)
references
References 23 publications
1
104
0
11
Order By: Relevance
“…Methodologic quality was assessed by two reviewers (KS and LH) using specific study design–related forms designed by the Dutch Cochrane Collaboration. The two observers independently assessed the included articles 8,10,11,14‐48 based on the recommended approach for assessing risk of bias in Cochrane reviews (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Methodologic quality was assessed by two reviewers (KS and LH) using specific study design–related forms designed by the Dutch Cochrane Collaboration. The two observers independently assessed the included articles 8,10,11,14‐48 based on the recommended approach for assessing risk of bias in Cochrane reviews (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…This difference seemed to be maintained over the 3-year period of the study. Grandi et al (2012) found for 28 patients with partial edentulism rehabilitated with two implant supported immediate restoration that when definitive platform-switched abutment was connect at time of surgery, there was statistically less bone resorption than in the group where abutments were removed for impression taken. Thus, many studies presently aim and surely will focus in the future on determination of the clinical and technical solutions, which must be undertaken to prevent recession of soft and hard tissues.…”
Section: Aggregatibacter Actinomycetemcomitans Tannerella Forsythensmentioning
confidence: 96%
“…However, other studies differ and show just a small number of cases with excellent clinical results 5,17 . In this study, the thickness of the surrounding soft tissues did not change significantly throughout the observation period (p=0.637).…”
Section: Perception Of Dental Professionalsmentioning
confidence: 94%
“…Currently, a less-invasive 4 approach is practiced in implantology due to the better understanding of bone biology and the development of new implants with surfaces that produce a better and quicker bone and peri-implant soft margin response, accelerating the rehabilitation. Thus, implants with immediate loading can be used in the majority of total, partial and even single rehabilitations [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation